(untitled) (MMIT Proceedings, 2025)
The article analyzes the potential of informatization as one of the key approaches to modernizing the education system. It highlights the role of modern information and communication technologies in enhancing the informatization level of the educational process and in developing information literacy among the population. The importance of digital tools in expanding educational opportunities is emphasized. Particular attention is given to the adaptation of teaching staff to the conditions of digital transformation in education, as well as to the main challenges associated with the implementation and use of modern technologies in the learning environment.